PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR: INVESTIGASI EMPIRIS PADA KARYAWAN HOTEL DI SURABAYA - Christy Widyawati; Verina Wijaya; Hendra Hendra; Rizki Adityaji; Wahyudi Henky Soeparto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
In the hospitality industry, the quality of service to customers is the most important thing. This requires the best participation of all employees for a company, which may lead to an increase of an individual performance. This study aims to examine the effect of organizational commitment toward organizational citizenship behavior (OCB) and employee performance. This research uses 144 employees of 3, 4 and 5 star hotels in Surabaya as the samples. The data was collected through questionnaires and processed using SmartPLS software. The findings generated from this study reveal that organizational commitment has a positive and significant effect on employee performance directly and through OCB as mediating factors. OCB itself also has a positive and significant effect on employee performance. The practical implication that can be suggested to hotel management is to enhance a holistic approach on the employees in order to increase emotional attachment of the employee toward the company. As the result, the employee sense of belonging on the company will increase, which make them also be responsible for the company's success. Keywords: organizational commitment, organizational citizenship behavior; employee performance